Clonal analysis of three morphologically distinct lymphomas occurring in the same patient. Issue 11 (November 1994) - McCormick, C; Philp, E; Mansi, J; Livni, N; McCarthy, K
Abstract : AIMS–To determine whether three morphologically distinct lymphomas (mucosa associated lymphoid tissue (MALT) lymphoma, monocytoid B cell lymphoma, and large cell anaplastic lymphoma), which occurred in the same patient, were in fact three morphological variants of the same lymphoproliferative process. METHODS–Previously described methods of clonal analysis using the polymerase chain reaction (PCR) were used to determine the pattern of rearrangements of the immunoglobulin heavy chain gene and the T cell receptor beta and T cell receptor gamma chain genes in the three lymphomas. RESULTS–All three morphological entities had identical patterns of gene rearrangements. CONCLUSIONS–This finding confirms the association between MALT lymphoma and monocytoid B cell lymphoma, and also provides evidence that large cell anaplastic lymphoma may not only arise de novo but may also be an end stage morphological picture in lymphoma progression.